2011
DOI: 10.1021/es1027585
|View full text |Cite
|
Sign up to set email alerts
|

Composition of Smoke Generated by Landing Aircraft

Abstract: A combination of techniques has been used to examine the composition of smoke generated by landing aircraft. A sample of dust from the undercarriage from several commercial airliners was examined with SEM/EDX (Scanning Electron Microscope/Energy Dispersive X-ray) to determine its elemental composition and also with an aerosizer/aerodisperser in order to measure the particle size spectrum. The observed size spectrum was bimodal with equal numbers of particles at peaks of aerodynamic diameter ∼10 μm and ∼50 μm. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
17
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(20 citation statements)
references
References 10 publications
0
17
0
Order By: Relevance
“…These results showed that the metals (Fe, Mn, and Zn) in the airport soils were associated with metal industry and tire wear particles (Bennett et al, 2011;Councell et al, 2004). The second component (PC2) had high factor loadings for metals, Cu, Pb, and Zn.…”
Section: Source Apportionmentmentioning
confidence: 88%
“…These results showed that the metals (Fe, Mn, and Zn) in the airport soils were associated with metal industry and tire wear particles (Bennett et al, 2011;Councell et al, 2004). The second component (PC2) had high factor loadings for metals, Cu, Pb, and Zn.…”
Section: Source Apportionmentmentioning
confidence: 88%
“…Some attention to the problem still exits mainly in aviation engineering research and environment quality areas. [16][17][18] Recently, the science and technology behind the pre-rotation have been systematically investigated and some solutions have been developed. [19][20][21][22][23][24] With current static wheel in landing, the ground friction has to spin the wheel to match the landing speed with the same tangential speed.…”
Section: Introductionmentioning
confidence: 99%
“…About one-third of rubber particles burn off under the skidding wheel is evaporates in the form of smoke, while the remaining proportion stays on the runway [6]. However, the rubber"s contact temperature is a function of the force of friction and the skidding speed, and there is no way to avoid a high force of friction.…”
Section: Introductionmentioning
confidence: 99%